Simultaneous Determination of Dolutegravir and Lamivudine in Human Plasma by LC-MS/MS: Pharmaceutical Sciences-Pharmaceutical analysis for Novel Drug Formulation - Bhadrua, Banothu; Rao, V.Venkata; Vidyadhara, Suryadevara (International Journal of Life Science and Pharma Research, 2021)
A rapid, simple, sensitive and selective LC-MS/MS method has been developed and validated for quanti? cation of the Dolutegravir and Lamivudine in plasma samples. The analytical procedure involves a liquid–liquid extraction method using Emtricitabine as an internal standard (IS). The precision and accuracy data have to fulfill the requirements for quantification of the analytes in biological matrices to generate data for bioequivalence and bioavailability investigations. The chromatographic separation was achieved on a Hypurity Advance (4.6, 50 mm, 5μ) column using a mobile phase consisting of 0.1% formic acid buffer–acetonitrile (20:80, %v/v) at ? ow rate of 0.8 mL/min. The API- 4000 LC-MS/MS was operated in the multiple-reaction monitoring mode using electrospray ionization. The total run time of analysis was 3 min and elution of Dolutegravir, Lamivudine and Emtricitabine (IS) occurred at 1.06, 1.84 and 0.92 min, respectively. A detailed validation of the method was performed as per the US Food and Drug Administration guidelines. The method was validated in terms of linearity, accuracy, precision, specificity, limit of detection and limit of quantitation. The standard curves found to be linear in the range of 0.10–30.0 ng/mL for Dolutegravir and 20.2–6026 ng/mL for Lamivudine, with a coef? cient of correlation of =0.99 for both the compounds. Dolutegravir and Lamivudine were found to be stable in a plasma stability studies, viz. bench-top, autosampler, re-injection, wet-extract and repeated freeze– thaw cycles. The coefficient of variation was =15% for intra- and inter-batch assays. The assay is suitable for pharmacokinetic study samples as demonstrated by its specificity, precision, accuracy, recovery, and stability characteristics.